2012
DOI: 10.1371/journal.pone.0044268
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Successful Cataract Surgery on Quality of Life, Household Income and Social Status in South India

Abstract: BackgroundTo explore the hypothesis that sight restoring cataract surgery provided to impoverished rural communities will improve not only visual acuity and vision-related quality of life (VRQoL) but also poverty and social status.MethodsParticipants were recruited at outreach camps in Tamil Nadu, South India, and underwent free routine manual small incision cataract surgery (SICS) with intra-ocular lens (IOL) implantation, and were followed up one year later. Poverty was measured as monthly household income, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 33 publications
4
100
0
3
Order By: Relevance
“…Cataract patients experienced decreased depressive symptoms and significant improvements in the vision-targeted quality of life after surgery. Similar with other studies, 6,7,11,12,32 patients in our study reported improved general vision, less difficulty with daily life activities and greater likelihood of engaging in social interactions following cataract surgery. Meanwhile, in comparing the changes from baseline to follow-up, cataract patients exhibited significant improvements in the RLVT.…”
Section: Discussionsupporting
confidence: 91%
“…Cataract patients experienced decreased depressive symptoms and significant improvements in the vision-targeted quality of life after surgery. Similar with other studies, 6,7,11,12,32 patients in our study reported improved general vision, less difficulty with daily life activities and greater likelihood of engaging in social interactions following cataract surgery. Meanwhile, in comparing the changes from baseline to follow-up, cataract patients exhibited significant improvements in the RLVT.…”
Section: Discussionsupporting
confidence: 91%
“…Suffice it to say that sight is restored almost immediately thus improving the patients' quality of life [19,20]. This observation may result in considering the procedure so casually without taking meticulous steps that ensure that there is quality in terms of postoperative visual acuity and patient's safety.…”
Section: More Than Just a Cataractmentioning
confidence: 99%
“…• India (Biggeri et al, 2012;Finger et al, 2012;Gershon & Srinivasan, 1992;Shore & Juillerat, 2012); • Nigeria (Eniola & Adebiyi, 2007); • Philippines (Lagerkvist, 1992b); • Vietnam (Shore & Juillerat, 2012).…”
Section: Lower-middle Income Countriesmentioning
confidence: 99%
“…There was variation in sample sizes. One study had a sample size greater than 500 participants (Shore & Juillerat, 2012), the sample size was between 251 and 500 in three studies (Biggeri et al, 2012;Finger et al, 2012;Nuri et al, 2012), and the remaining ten studies had a sample size of less than 250. All studies designated the individual/household as the unit of analysis.…”
Section: Upper-middle Income Countriesmentioning
confidence: 99%
See 1 more Smart Citation